Использование кластеризации при выборе структуры объекта управления - Коваль, П.Н. (Міжнародний науково-навчальний центр інформаційних технологій і систем НАН та МОН України, 2010)
The stage of preliminary analysis of dates is considered. There is proposed to use the clustering over short distance in multi measure space of the parameters. The probability formula of error is shown. The method of strike off non information signs from parameters set is created.